“WELCOMING THE ORPHANS OF GLOBALISATION”: The Case for Seafarers’ Ministry - Zuidema, Jason; Walker, Kevin (Science et Esprit, 2020)
More than 90% of the products and goods we consume on a daily basis made their way to us principally by sea. Yet, increasingly, port areas and the ships that serve them are not commonly frequented or understood. Completely unknown are the more than 1.75 million seafarers who sail those ships. Though they connect us to the goods of the world, these seafarers live disconnected from their families and home cultures. Recognizing this disconnection in the lives of seafarers, an ecumenical network of Christian chaplaincies around the world exists to provide a welcome in foreign ports. After outlining the basic rationale, work, and history of seafarers’ welfare, this essay elicits the practical examples of internet access for seafarers and of ministry of presence as examples of care that have shaped seafarers’ ministry. These examples frame our understanding of the chaplain’s work: the chaplain’s passion, character or theological understanding alone are not sufficient. We argue that more cooperation, training, and consistency in work are necessary for long-term effectiveness in seafarers’ ministry as in any other workplace chaplaincy.